Use of Novel Decellularized Cadaveric Dermis (DCELL) in Single-Stage Resection and Reconstruction of Nonmelanomatous Skin Cancer of the Head and Neck - Mantelakis, Angelos; Kostantinos, Argiris; D'Souza, Alwyn; Joshi, Anil (Facial Plastic Surgery, 2021)
Reconstructive options in nonmelanomatous skin tumors of the head and neck region are limited in the frail, elderly patient group, where split skin thickness or full thickness grafts may not be a viable option. This study examines the use decellularized cadaveric dermis (DCELL), an acellular dermis product produced in the United Kingdom for the reconstruction of these skin defects. This was a single-center, prospective study of patients undergoing single stage wide local excision of nonmelanomatous skin cancer and reconstruction with decellularized dermis. Our inclusion criteria included any patient that required a curative excision but had risk factors where conventional local flap or free tissue transfer could have a potential adverse outcome. Thirty-seven wounds were treated with DCELL in 31 patients. Mean age was 81.6 years (range 61–94 years) and at the time of operation, 25 patients (80.7%) were ASA 3 or above. The scalp was the most common anatomical area operated on (n = 28, 75.7%). The overall proportion of wounds with complete closure was 89.2% (33 out of 37 wounds), with a failure rate of 10.8% (four complete graft failures). Device-related complications included one episode of crusting over the graft which resolved with topical antibiotics, and a hypertrophic scar over the wound edges. Cosmesis was satisfactory in all cases. DCELL demonstrated a very good take rate with equally satisfactory cosmetic outcomes in patients where standard reconstructive approaches may have adverse outcomes. Further research is needed to better define its role in the management of these skin cancers.
Keywords: allograft; skin cancer; head and neck; acellular dermal matrix; decellularized dermis